Katie's way - Perry, Marta (Perry, Marta. Pleasant Valley, 2011)
After opening a quilt shop in Pleasant Valley, Katie Miller's efforts to attract both Amish and Englisch customers is greeted by acts of vandalism and she seeks support and comfort from Caleb Brand, owner of the furniture store next door.